BİR MUTASAVVIF OLARAK KUŞEYRÎ’NİN KELAMİ GÖRÜŞLERİ - İsmail Şık (İslami İlimler Dergisi)
Kuşeyrî who adopted to Ashari theology’understanding, have important effect to became systematized in the İslamic Sufism’tradition. Not only He presented detalied information and opoinion but also in his works that they interested with Asharism is from Ehl-ı Sunne’theology scholls have contiributed to spread and know. Kuşeyri adopted to principle of true beleif and true action, he stressed strong beleif that leaned to Quran. His sensetiveness in this subject signed diaologue that to be necessary betwen İslamic Sufism and Theology sciences